The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1360-0443.2011.03447.x
|View full text |Cite
|
Sign up to set email alerts
|

Social gradient in initiation and transition to daily use of tobacco and cannabis during adolescence: a retrospective cohort study

Abstract: Adolescents from the highest family socio-economic status categories are at risk for tobacco and cannabis experimentation but are less prone to engage in daily use. Psychological and social mechanisms that inhibit transition to daily use should be investigated, including school attainment and performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
60
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 65 publications
11
60
1
Order By: Relevance
“…As with other studies conducted in different settings, we found that participants who did not achieve a high school degree, completed vocational (rather than general) education or experienced grade retention were more likely to smoke persistently and at high levels [13,14,[36][37][38]. Smoking is a social behavior -particularly in adolescence -and this finding highlights higher acceptability of tobacco use in socioeconomically disadvantaged groups [39].…”
Section: Individual Characteristics and Tobacco Use Trajectoriessupporting
confidence: 82%
See 3 more Smart Citations
“…As with other studies conducted in different settings, we found that participants who did not achieve a high school degree, completed vocational (rather than general) education or experienced grade retention were more likely to smoke persistently and at high levels [13,14,[36][37][38]. Smoking is a social behavior -particularly in adolescence -and this finding highlights higher acceptability of tobacco use in socioeconomically disadvantaged groups [39].…”
Section: Individual Characteristics and Tobacco Use Trajectoriessupporting
confidence: 82%
“…In particular, our data confirm the predictive role of early tobacco and cannabis initiation, which are associated with elevated odds of persistent high-level smoking as well as high-level smoking followed by cessation [13]. Early substance use initiation could be indicative of a propensity for addiction -reflecting both genetic and environmental influences [29,30], which may lead to longterm patterns of substance use.…”
Section: Individual Characteristics and Tobacco Use Trajectoriessupporting
confidence: 77%
See 2 more Smart Citations
“…Instead, many levels of use should be studied since the progression of use may occur in stages, from experimentation to regular use, as described for cannabis use (Becker, 1963) and alcohol (Graham, Collins, Wugalter, Chung, & Hansen, 1991). As a consequence, the relationship with F-SES may vary at each stage, or for each frequency of use: this kind of relationship has been found for the progression from tobacco and cannabis experimentation to daily use (Legleye, Janssen, Beck, Chau, & Khlat, 2011), but no similar study has been conducted for alcohol use.…”
Section: Introductionmentioning
confidence: 99%